Perioperative drug treatment in pancreatic surgery: a systematic review and meta-analysis - Rompen, Ingmar F.; Merz, Daniela; Alhalabi, Karam T.; Klotz, Rosa; Kalkum, Eva; Pausch, Thomas; Strothmann, Hendrik; Probst, Pascal (Journal of Clinical Medicine, 2023)
Introduction: Pancreatic resections for malignant or benign diseases are associated with major morbidity and changes in physiology. To reduce perioperative complications and enhance recovery, many types of perioperative medical management have been introduced. The aim of this study was to provide an evidence-based overview on the best perioperative drug treatment. Methods: The electronic bibliographic databases Medline, Embase, CENTRAL, and Web of Science were systematically searched for randomized controlled trials (RCT) evaluating perioperative drug treatments in pancreatic surgery. The investigated drugs were somatostatin analogues, steroids, pancreatic enzyme replacement therapy (PERT), prokinetic therapy, antidiabetic drugs, and proton pump inhibitors (PPI). Targeted outcomes in each drug category were meta-analyzed. Results: A total of 49 RCT were included. The analysis of somatostatin analogues showed a significantly lower incidence of postoperative pancreatic fistula (POPF) in the somatostatin group compared to the control group (OR 0.58, 95% CI: 0.45 to 0.74). The comparison of glucocorticoids versus placebo showed significantly less POPF in the glucocorticoid group (OR 0.22, 95% CI: 0.07 to 0.77). There was no significant difference in DGE when erythromycin was compared to placebo (OR 0.33, 95% CI: 0.08 to 1.30). The other investigated drug regimens could only be analyzed qualitatively. Conclusion: This systematic review provides a comprehensive overview on perioperative drug treatment in pancreatic surgery. Some often-prescribed perioperative drug treatments lack high quality evidence and further research is needed.
Gesehen am 28.03.2023